The Relationship Of Achievement Motivation And Self-Confidence To College Student’s Physical Fitness - Sungkawa, Muhamad Guntur Gaos; Yudho, Firdaus Hendry Prabowo; Dapa, Muhammad; Rahadian, Adi (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
The purpose of this study was to determine the correlation of the level of achievement motivation of physical education students in higher education to the level of their physical fitness. The method used in this study is a correlational analysis of two variables between achievement motivation and the physical condition of the samples. The subjects in this study were 24 college students, males, and females. The instrument used to obtain motivational data for the samples was an achievement motivation questionnaire consisting of 38 questions, and the Indonesian Physical Fitness Test (TKJI) to measure the physical fitness level of the samples. Data analysis uses statistical software applications that aim to obtain descriptive and inferential results to be able to conclude quantitative research results. The results of this study indicate that there is an insignificant relationship between achievement motivation and self-confidence in the sample’s physical fitness in both males and females.Keywords: Achievement Motivation, Self Confidence, Physical Fitness, Physical Education, Sports Psychology.